Rhetorical Strategies in Political Campaign Banners: Language Use in the 2024 Election in Pekanbaru City - Perizga, Andiana; Nurhaliza; Charlina, Charlina; Deani, Amira; Putri, Ghina’a Jayanthi; Wahyudin, Syabrina (GERAM (Gerakan Aktif Menulis), 2026)
This study aims to analyze the rhetorical strategies employed in campaign banners of legislative candidates in the 2024 General Election in Pekanbaru City using the Aristotelian rhetorical framework of ethos, pathos, and logos. The study adopts a qualitative approach with a descriptive method based on textual analysis of the verbal and visual messages contained in campaign banners. Data were collected through stratified purposive sampling and analyzed to identify the forms, dominant tendencies, and implications of rhetorical strategy use in visual-based political campaigning. The findings indicate that ethos is the most dominant rhetorical strategy. Candidates’ credibility is constructed through the emphasis on personal identity, political track records, social and local affiliation, religious legitimacy, and narratives of integrity and leadership responsibility. Pathos functions as a supporting strategy manifested through political promises, personal and religious appeals, as well as creative humor to establish emotional closeness with voters. Meanwhile, logos appears in a limited and simplified form, primarily through references to technocratic capacity and institutional functions, indicating the existence of rational constraints inherent in campaign banners as static visual media. This study concludes that the ethos–pathos–logos hierarchy in campaign banners is contextual and shaped by media characteristics as well as the social configuration of the local community.